2015
DOI: 10.1103/physrevc.92.064615
|View full text |Cite
|
Sign up to set email alerts
|

Multinucleon exchange in quasifission reactions

Abstract: Nucleon exchange mechanism is investigated in the central collisions of 40 Ca + 238 U and 48 Ca + 238 U systems near the quasi-fission regime in the framework of the Stochastic Mean-Field (SMF) approach. Sufficiently below the fusion barrier, di-nuclear structure in the collisions is maintained to a large extend. Consequently, it is possible to describe nucleon exchange as a diffusion process familiar from deep-inelastic collisions. Diffusion coefficients for proton and neutron exchange are determined from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…An important message here is that those IQF processes emerge as a main reaction outcome in TDHF. Since larger effects of fluctuations and correlations, that give rise to a wider fragment mass distribution, are expected in such damped collisions [106,[141][142][143], novel IQF processes may pave new pathways to unexplored territories in the nuclear chart far away from the stability.…”
Section: B Quasifission Processesmentioning
confidence: 99%
“…An important message here is that those IQF processes emerge as a main reaction outcome in TDHF. Since larger effects of fluctuations and correlations, that give rise to a wider fragment mass distribution, are expected in such damped collisions [106,[141][142][143], novel IQF processes may pave new pathways to unexplored territories in the nuclear chart far away from the stability.…”
Section: B Quasifission Processesmentioning
confidence: 99%
“…The effects of two-body dissipation on reactions of heavy systems using the TDDM [38,39], approach have also been recently reported [40,41]. Here we discuss some recent results using the SMF method [42].…”
Section: Introductionmentioning
confidence: 98%
“…The initial conditions of the single-particle density matrices associated with the ensemble Slater determinants are specified in terms of the quantal and thermal fluctuations of the initial state. For a detailed description of the SMF approach, we refer to [37,[42][43][44]. In extracting transport coefficients for nucleon exchange, we take the proton and neutron numbers of projectile-like fragments Z λ 1 , N λ 1 as independent variables, where λ indicates the event label.…”
Section: Nucleon Diffusion Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, it has been demonstrated that the SMF approach alleviates the drawbacks of the standard mean-field approach and improves the description of nuclear collisions dynamics including fluctuation mechanism of the collective motion [30,[32][33][34][35][36][37]. Most applications have been carried out for collisions where a di-nuclear structure is maintained.…”
Section: Introductionmentioning
confidence: 99%